Decoding the learning curve of non-descent vaginal hysterectomy in the era of laparoscopy- experience at a Zonal Hospital - Sharma, Shikha; Husain, Jafar; Jain, Anshul; Bhaskaran, Sruthi; Singh, Raj; Pandey, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Despite of the increasing popularity of laparoscopic hysterectomy, vaginal route still stays pertinent. Non descent vaginal hysterectomy (NDVH) involves d steep learning curve and hence, should be a fundamental part of every Gynaecology residency program. Objective of the study was to assess the learning curve of NDVH surgery skill at a Military Zonal Hospital by a single Specialist over a period of two years. Methods: Retrospective study conducted at Military Hospital, Agra between June 2015 to June 2017 on 30 patients who underwent NDVH for benign gynaecological conditions. Results: The average blood loss was noted to reduce from a mean of 285ml (±108.94) in the first 20 cases (Group 1) to 227ml (±110.89) in the next 10 cases (Group 2) despite of the average uterine size increasing from 8.5 (±1.43) weeks in Group 1 to 10.2 (±2.39) weeks in Group 2. The average time taken in minutes was also seen to reduce from 89.75 (±12.62) in Group 1 to 70.5 (±16.50) in Group 2 indicating an improvement of surgical skills. The average 24 hr post-operative haemoglobin fall of 0.8gm% was similar between the two groups. Conclusions: Acquiring NDVH skills is a slow but rewarding process. NDVH involves no incisions, no elaborate set-up, avoids complications of general anaesthesia and pneumo-peritoneum and displays similar results as of laparoscopy. In limited resource countries vaginal route may be the only available minimally invasive option for hysterectomy. Hence, it’s pertinent that Gynecologists are trained in the same.